Toward a General Theory of Research Ethics - MENIKOFFF, JERRY (The Hastings Center report, 2007)
On the one hand, based on the importance of personal autonomy, we require the informed consent of subjects who have decisional capacity, and provide special protections to those who lack such capacity. Franklin Miller and Alan Wertheimer have produced a rich, elegantly argued essay suggesting that much of research ethics, as it relates to studies intended for adults with decisional capacity, can be derived from a single intriguing concept.